PENGARUH KELANGKAAN MINYAK GORENG TERHADAP PENETAPAN HARGA JUAL DAN PENGELOLAAN LABA PADA UMKM USAHA MAKANAN DI DESA CIKEMBAR - Muhamad Hisab; Idang Nurodin (Jurnal Ilmu Akuntansi, 2022)
The scarcity of cooking oil that occurred starting at the end of 2021 makes most food business msme actors, especially by frying, have to make various efforts to stay afloat and run their businesses. One of the factors of selling price fixing and profit management is the availability of raw materials from production. This research aims to determine the influence of the phenomenon of scarcity of cooking oil on the determination of selling prices and also profit management that occurs in food business msmes in Cikembar Village. The variables used in this study were the scarcity of cooking oil, selling price fixing and profit management either partially or simultaneously or together. This research is quantitative research. By using questionnaires and processed with statistical calculations using SPSS for windows version 25. The hypothesis is established using a two-party test (two tailed). Analytical techniques used normality test, heteroskedasticity, correlation, correlation analysis, simple linear regression analysis, determination coefficient analysis, t test and F test. This research shows that the scarcity of cooking oil that occurs has a significant effect on selling price determination and also profit management, both partially and simultaneously.